Validation of the Brief Index of Sexual Functioning for women and men (BISF-W and BISF-M) in an Italian sample - Panzeri, Marta; Ronconi, Lucia; Fontanesi, Lilybeth (Frontiers in Psychology, 2024)
Introduction The Brief Index of Sexual Functioning for Women (BISF-W) is an international 4-factors tool assessing qualitative and quantitative aspects of sexual experiences in women, both in clinical and experimental settings. The present research aims at validating an Italian version of the BISF-W, to develop a BISF version for men (BISF-M) to fill the gap in the existing sexual function evaluation tools in Italy and to analyze gender and age groups differences in the BISF factors. Methods The research included 6,355 women, aged from 18 to 65 (M = 34.94, SD = 10.52) and 2,207 men, aged from 18 to 80 (M = 38.25, SD = 13.67), who completed the BISF-W and BISF-M. The Quality of Marriage Index (QMI) was administrated to both samples for testing divergent validity, while Female Sexual Function Index (FSFI) and the International Index of Erectile Function (IIEF) were administered for testing convergent validity. Correlation analysis, MANOVA between gender and age and Confirmatory Factor Analysis were conducted. Results The CFAs confirmed that the proposed 4-factor model (Dyadic, Solitaire and Anal Sexuality, and Sexual Difficulties) is suitable both for the BISF-W and the BISF-M, demonstrated strong psychometric properties for assessing sexual functioning in both genders, with dyadic sexuality being the most important factor. MANOVA analysis showed significative differences in the factors’ scores, according to gender and age. Discussion The BISF-W and the BISF-M are promising tools to address sexual functioning in individuals and couples, both in clinical and non-clinical settings. Gender and age differences are discussed regarding the potential use of BISF in the therapeutic context.